Die inhoud en die doel van die Nederduitsch Hervormde Kerk se bediening, met verwysing na die ampte - Breytenbach, J. H. (Hervormde teologiese studies, 1991)
The substance and purpose of the ministry of the Nederduitsch Hervormde Kerk, with reference to ecclesiastical offices. For close on a decade, the Nederduitsch Hervormde Kerk van Afrika has been debating the issue of appropriate structures and patterns for its ministry. In this article it is argued that the debate not only reflects dissatisfaction with structures and patterns, but also brings to light dissatisfaction with the substance and purpose of the ministry of the Word as such. The ministry of the church should be understood in the light of the essence of being a church, which resides in the fact that the church belongs to the Lord. It is possible to belong to the Lord only on the basis of faith in the Word of God. The church, therefore, has one ministry only: the ministry of the Word. Appropriate ecclesiastical offices, structures and patterns are those that minister the Word.